ANALYSIS OF OPERATING RELIABILITY OF A STARTER-GENERATOR SYSTEMS IN CARS - Кравченко, Александр; Титаренко, Владимир; Шумлякивський, Владимир (SWorldJournal, 2021)
Abstract. The current study presents the results of reliability analysis of starter-generator systems used in the lineup of modern cars. The components of starters and generators that are most vulnerable to adverse operating factors and significantly aff